Surgical treatment of achalasia and the option of laparoscopic surgery - Perrier, José Pedro; Fernández, Miguel; Sosa, María Cristina (Cirugía del Uruguay, 2000)
Between 1978 to 1999, 12 patients with achalasia underwent surgery, using laparoscopic approach in tour of which. The mean age was 42,9 years. The group was composed of 8 fema/es and 4 males. Al/ cases were idiopathic. Eighty three percent had had one ar more episodes of dilatation, with symptomatic period prior to surgery of 4 years and 10 months